Pengaruh Brief Counseling Terhadap Aktifitas Fisik pada Pasien Hipertensi Di RSUD Dr. H. Moch Ansari Saleh Banjarmasin - Saftia Aryzki; Riza Alfian (Jurnal Sains Farmasi & Klinis, 2016)
Behavior lack of physical activity can lead to failure to achieve the goal of therapy in hypertensive patients. The study aims to determine the effect of brief counseling-5A toward physical activity in hypertensive patients in hospital outpatient Moch. Ansari H. Saleh Banjarmasin. Quasi-experimental study using two group pretest and posttest with prospective data collection. Subjects who met the inclusion criteria a number of 68 patients into two groups: 34 patients and 34 intervention patients did not intervene. Exclusion criteria were patients with the condition of pregnancy, deaf and was not present at the next visit. The collection of data through interviews and questionnaires International Physical Activity Questionnaire (IPAQ). The results showed the treatment group experienced significant changes, the average value of Δ1 increases = 243.60 ± 1237.68 and p = 0.00, which Δ2 = 90.42 ± 319.95 and p = 0.31. It was concluded that brief counseling-5A can positively change the behavior of the patient in physical activity in the treatment group.